Prophylactic cranial irradiation for limited‐stage small‐cell lung cancer in the magnetic resonance imaging era - Lihua Pan; Xingwen Fan; Lifang Wang; Yihua Wang; Yaqi Li; Yingshan Cui; Hong Zheng; Qiong Yi; Kailiang Wu (Cancer Medicine)
Abstract Background We investigated the role of prophylactic cranial irradiation (PCI) in limited‐stage small‐cell lung cancer (LS‐SCLC) according to tumor response in the magnetic resonance imaging (MRI) era. Methods We retrospectively evaluated patients with LS‐SCLC without brain metastases (BMs) on MRI who achieved either complete response (CR) or partial response (PR) after initial chemoradiotherapy at our center from 2006 to 2017. Results This study comprised 116 patients (median age, 58 years; men, 92; women, 24). After initial chemoradiotherapy, 53 patients achieved CR, while 63 patients achieved PR. Eighty‐three patients received PCI. Patients who received PCI had better overall survival (OS, 5‐year: 52.5% vs. 35.1%; p = 0.012) and progression‐free survival (PFS, 5‐year: 45.0% vs. 28.2%; p = 0.001) and a lower incidence of BMs (5‐year: 18.3% vs. 39.4%; p = 0.010). In the subgroup analysis, PCI improved OS (5‐year: 67.8% vs. 46.7%, p = 0.005) and PFS (5‐year: 65.2% vs. 35.0%, p = 0.021) and decreased BM risk (5‐year: 12.1% vs. 52.4%, p = 0.002) for patients with CR. However, PCI had no benefit (5‐year OS: 40.5% vs. 35.6%, p = 0.763; 5‐year BMs: 24.6% vs. 31.9%, p = 0.561) for patients with PR. Conclusions Tumor response remained an important factor for selecting patients for PCI in the MRI era. PCI should be recommended for patients with LS‐SCLC who achieve CR after initial thoracic chemoradiotherapy.